Space-Temporal Processing of Low Frequency Electric and Magnetic Signals in a Linear Medium-Analysis and Application in Medical Therapy - Dimitrov, D. Tz.; Dimitrov, A. D. (Elektronika ir Elektrotechnika, 2014)
An optimization of parameters of movement of ions of alive tissues and also parameters of movement of ions of different drug implemented in alive tissues can be provided using appropriate parameters of external low frequency electromagnetic field on the basis of mathematical results. The obtained engineering basis for optimization of the process of medical therapy is the main result of the present investigation. A new mathematical model for description and investigation of movement of ions (including their velocity) in alive tissues under influence of external low frequency electromagnetic field is performed in the article. DOI: http://dx.doi.org/10.5755/j01.eee.20.1.3292